(untitled) (Scientific journal of the Fergana State University, 2026)
In this research, we have investigated the bioecological properties of Cistanche salsa plants grown in soil and the climatic conditions of Khorezm region. We analyzed dispersion location, mutual dependencies with different plants, and its adaptation to soil and climatic factors. In addition, the growth stages, and ecological and environmental significance of the Cistanche salsa plant are reported. The research also covers scientific analysis on the role of this parasite in the desert and semi-desert ecosystems and its adaptation to the environment.